Inactivation of foodborne viruses by the cold plasma technology - Pexara, Andreana (Journal of the Hellenic Veterinary Medical Society, 2022)
Cold plasma (CP) is an innovative non-thermal food processing method. CP refers to a partially or completely ionized gas containing reactive chemical species, which are active against microorganisms, including viruses or enzymes of foods. CP has a minimal effect on the quality attributes of foods and can also elongate the shelf life of foods. Foodborne outbreaks caused by viruses have been increased in various countries in recent years. The research works on the inactivation effect of CP against viruses including foodborne viruses have been also increased in recent years. The most important foodborne viruses are human norovirus (HuNoV) and hepatitis A virus (HAV), involved in several outbreaks worldwide. Human astrovirus (HAstV), human adenovirus (HuAdV), Aichi virus (AiV), sapovirus (SaV) and enterovirus (EV) are also notable foodborne viruses and were associated in sporadic cases. The CP treatment proved efficient for the inactivation of foodborne viruses such as HuNoV and HAV. The present work reviews the CP as a non-thermal food processing technology and present the published data on the effect of CP process on foodborne viruses in foods.